2023
DOI: 10.1002/cam4.6494
|View full text |Cite
|
Sign up to set email alerts
|

Influence of menopause on chemotherapy‐induced nausea and vomiting in highly emetogenic chemotherapy for breast cancer: A retrospective observational study

Takashi Yokokawa,
Kenichi Suzuki,
Daiki Tsuji
et al.

Abstract: BackgroundFemale sex and younger age are reported risk factors for chemotherapy‐induced nausea and vomiting (CINV) in highly emetogenic chemotherapy, but the underlying mechanism has not been elucidated. The purpose of this study was to clarify the impact of menopause on CINV.MethodsThis retrospective observational study analyzed data from consecutive patients who received their first cycle of perioperative anthracycline‐based chemotherapy for breast cancer between January 2018 and June 2020. The endpoints wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Menopause (age at menopause): Late menopause increases breast cancer risk due to prolonged hormonal exposure ( 111 ). links menopausal hormonal changes to chemotherapy side effects severity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Menopause (age at menopause): Late menopause increases breast cancer risk due to prolonged hormonal exposure ( 111 ). links menopausal hormonal changes to chemotherapy side effects severity.…”
Section: Resultsmentioning
confidence: 99%
“…found that genetic variations can influence an individual's susceptibility to radiation toxicity (106). discusses lung cancer risk post-radiotherapy (111); links menopause to chemotherapy side effects; and (22) reported a high radiodermatitis incidence (98.2%) in breast cancer patients undergoing radiotherapy, with BMI and statin use affecting severity, and hydrogel showing protective effects. • Exposure to chemicals: Chemicals like endocrine disruptors may disrupt hormonal balance, potentially contributing to breast cancer (105).…”
Section: Environmental Factorsmentioning
confidence: 99%